2020
DOI: 10.21203/rs.3.rs-45412/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The burden of anxiety among people living with HIV during the COVID-19 pandemic in Pune, India

Abstract: Introduction: Globally, India has the third largest population of people living with HIV (PLHIV) and the second highest number of COVID-19 cases. Anxiety is associated with antiretroviral therapy (ART) nonadherence. It is crucial to understand the burden of anxiety and its sources among Asian Indian PLHIV during the COVID pandemic, but data are limited.Methods: During the first month of government mandated lockdown, we administered an anxiety assessment via telephone among PLHIV registered for care at a public… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Table 1 summarizes the main characteristics of the 10 studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. A total sample of 3127 PLHIV from seven countries was included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 summarizes the main characteristics of the 10 studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. A total sample of 3127 PLHIV from seven countries was included in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…There were six studies [ 36 , 37 , 38 , 41 , 44 , 45 ] reporting data related to anxiety among PLHIV. Five of them [ 36 , 37 , 38 , 44 , 45 ] presented the number of cases with severity scales, and data on anxiety in one study [ 41 ] were reported in the mean score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mortality rate from suicide is 1%, with suicide mortality rates declining post ART initiation [ 54 ]. Anxiety disorders, particularly generalized anxiety disorder (GAD), are also commonly comorbid conditions in PLWH, with 25–33% experiencing clinically significant anxiety [ 47 , 57 , 63 ]. Internalized stigma has a significant indirect effect on anxiety through self-blame [ 49 ].…”
Section: Discussionmentioning
confidence: 99%